Upaya Peningkatan Motivasi Belajar Baca al-Qur’an Siswa Melalui Learning Together Technique of Cooperative Learning Method - Ratna Untari (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Association of Muslim Community in ASEAN (AMCA), 2021)
This study aims to describe and analyze in-depth the efforts to improve the learning motivation of reading al-Qur’an of students in class XI Multimedia by learning together techniques of cooperative learning methods at SMK Negeri 1 Mlarak Ponorogo. The research approach used was a classroom action research model of Kemmis and Taggart in the form of a spiral consisting of three cycles. Each cycle consists of planning, action, observation, and reflection. Data collection techniques used written and oral tests, observation, and audio recordings. Then, the research data will be analyzed by data reduction, data display, and conclusions. This study proposes the findings that: learning together technique of cooperative learning method has a positive impact in increasing the motivation to learn to read al-Qur'an students of class XI Multimedia at SMK Negeri 1 Mlarak Ponorogo. This is indicated by the increase in student learning completeness in each cycle, namely: cycle 1 (41.93%), cycle II (67.74%), cycle III (100%). In addition, the learning together technique of cooperative learning method makes students feel that they get attention and the opportunity to convey opinions or ideas and questions related to reading the al-Qur'an. The application of learning together techniques of cooperative learning methods has a positive effect in increasing student motivation in reading al-Qur'an.